EDUCATION AND TRAINING OF INFANT AND YOUNG CHILD FEEDING (IYCF) PRACTICES AS AN NEFFORT TO PREVENT STUNTING IN THE WORKING AREA OF BONEROMBO PUBLIC HEALTH CENTER IN 2023 - Hastuti, Wa Ode Sriy; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRAK This research aimed to address stunting, a chronic nutritional problem influenced by long-term malnutrition and factors related to maternal conditions, fetal development, and early childhood. Recognizing the crucial role of cadres and parents, the study focused on enhancing their knowledge and skills, particularly in Infant and Young Child Feeding (IYCF). The community activity aimed to improve family health by providing education and training to Integrated Health Post cadres and mothers, specifically in preparing complementary feeding with locally sourced ingredients. Using a quantitative experimental approach with a pre-experimental one-group pre-test design, 40 respondents were selected through proportional stratified random sampling. The findings showed a significant impact on maternal knowledge, with 67.5% having low knowledge before the intervention, reducing to 20% post-intervention. Conversely, the percentage of mothers with high knowledge increased from 32.5% before to 80% after the intervention. The Paired T-test confirmed the effectiveness of the intervention at Bonerombo Public Health Center, North Buton Regency (p-value: 0.000 < 0.05). It is recommended to continue and expand similar educational interventions due to the demonstrated positive impact on maternal knowledge. Incorporating qualitative research methods, such as interviews or focus groups, may provide deeper insights into participants' experiences, enriching the understanding of the community's response. This holistic approach can contribute to developing more targeted and culturally sensitive health education programs. Keywords: Integrated Health Post Cadres, Stunting, Toddler, Mother’s Knowlegde